2016
DOI: 10.1039/c5cp07906c
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide reduction on Ir(111): stable hydrocarbon surface species at near-ambient pressure

Abstract: Stable hydrocarbon surface species in the carbon dioxide hydrogenation reaction on Ir(111) were identified by means of infrared-visible sum-frequency generation vibrational spectroscopy and X-ray photoelectron spectroscopy under near-ambient pressure conditions (0.1 mbar). By introducing gas phase binary and ternary mixtures of CO2, CO, and H2 into the reaction chamber, stable ethylidyne and ethynyl species were found at the metal surface above 425 K, in remarkable analogy with that observed during the ethylen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(60 citation statements)
references
References 49 publications
2
57
0
Order By: Relevance
“…3–6 ) identifies four contributions at 1986, 1992, 2005, and 2011 cm −1 . The SFG signal was deconvoluted by means of an established least-square fitting procedure 32 , according to an effective description of the nonlinear second-order susceptibility (the complete set of fitting parameters is reported in Supplementary Tables 1 and 2 ). The surface density of the Fe centers is very low due to the large size of the FePc molecules (about 0.03 ML with respect to the underlying Ir metal surface).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…3–6 ) identifies four contributions at 1986, 1992, 2005, and 2011 cm −1 . The SFG signal was deconvoluted by means of an established least-square fitting procedure 32 , according to an effective description of the nonlinear second-order susceptibility (the complete set of fitting parameters is reported in Supplementary Tables 1 and 2 ). The surface density of the Fe centers is very low due to the large size of the FePc molecules (about 0.03 ML with respect to the underlying Ir metal surface).…”
Section: Resultsmentioning
confidence: 99%
“…IR-Vis sum-frequency generation vibronic spectroscopy measurements were performed in a dedicated setup 32 . A UHV system with a base pressure of 5 × 10 −11 mbar hosts standard surface science preparation and characterization techniques, and it is directly connected to a high-pressure cell for in situ IR-Vis SFG spectroscopy.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of the N-species on the carbon substrate both stabilizes the active Fe(II) centers hindering further reduction of Fe, thus inhibiting the hydrogen evolution, and allows coordination of the reactive CO 2 -related species related with the liquid phase [142]. Interestingly, it is found that the latter (H 2 CO 3 , HCO 3 − , CO 3 − ) consistently differ with respect to their counterpart in the case of the solid/gas reaction [68][69][70][71][72][144][145][146]. Metal-nitrogen coordinated electrocatalytic systems offer the capability of electron donation/ withdrawal to/from the carbonaceous ligand, thus with improved and tunable activity [147][148][149][150].…”
Section: 1mentioning
confidence: 99%